Tingkat Pengetahuan Guru PJOK Tentang Penanganan Pertama Cedera dalam Pembelajaran dengan Metode Rest Ice Compress Elevation (Rice) di SMP dan SMA Kota Bandar Lampung - Rizki Farhan Annafi (Journal of Creative Student Research, 2025)
Physical education is the development of physical fitness, motor skills, social skills, moral behavior, aspects of healthy living, and the introduction of a clean environment through systematically planned physical activities to achieve national education goals. There are many factors that can cause student injuries. However, some teachers lack knowledge about injury prevention and first aid. This can worsen injuries that should be treated immediately. The aim of this activity is to determine the level of knowledge of sports teachers regarding first aid for injuries using the RICE method. Descriptive research method. The population of this study were all physical education teachers in middle and high schools in Bandar Lampung. The sampling is total sampling. Based on the results of the questionnaire that was filled in by all respondents, it was found that 83% of respondents had good knowledge. The conclusion from this activity is that violence against mothers and children must be opposed to prevent the impact that will occur on children. Having a good knowledge of how to treat injuries using the RICE (Rest, Ice, Compression, Elevation) method can help students in the future when they are injured during school hours